2018
DOI: 10.3389/fcvm.2018.00104
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Events After Transcatheter Aortic Valve Implantation

Abstract: Transcatheter aortic valve implantation (TAVI) has emerged as an alternative less invasive treatment for patients with symptomatic severe aortic stenosis. Despite the technological development and knowledge improvement in recent years, neurological complications remain a concern, especially with the expansion of the technique toward younger and lower risk patients. Clinical cerebrovascular events have an important impact on patients' morbidity and mortality with a multifactorial origin. While cerebral microemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 89 publications
0
42
0
3
Order By: Relevance
“…Nevertheless, prevention strategies to decrease CVE rate are critical prior to expand TAVI indication to younger, lower risk patients. Several imaging and histopathological studies have demonstrated that the majority of CVE after TAVI have an embolic origin, from debris embolization or thrombus formation (9). Embolic protection devices (EPD) have emerged as a mechanical protection strategy to prevent these emboli to reach the cerebral vasculature and decrease the associated neurological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, prevention strategies to decrease CVE rate are critical prior to expand TAVI indication to younger, lower risk patients. Several imaging and histopathological studies have demonstrated that the majority of CVE after TAVI have an embolic origin, from debris embolization or thrombus formation (9). Embolic protection devices (EPD) have emerged as a mechanical protection strategy to prevent these emboli to reach the cerebral vasculature and decrease the associated neurological effects.…”
Section: Introductionmentioning
confidence: 99%
“…At near valve closure, flow dynamics can be considered analogous to transient valve stenosis, whereby regurgitation is increasingly constrained until complete, motionless, closed-valve conditions occur. During brief crucial moments preceding valve closure, localized prothrombotic microenvironments may be relevant to generation of high velocity leakage jets, flow unsteadiness, valve flutter, cyclic variability of PDVA, turbulence, and excessive shear forces that may induce blood element damage [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These influences may impact multiple valve types for:…”
Section: Resultsmentioning
confidence: 99%
“… conduction abnormalities,  reduced valve leaflet mobility, sub-clinical thrombosis [17,23,[26][27][28]30],  potential for pannus formation,  silent cerebral micro-infarction [24,25],  acute and sub-acute embolic stroke and other adverse cerebrovascular events including TIA [24,26],  cavitation and high intensity trans-cranial signals (HITS) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Die periprozedurale Schlaganfallrate in randomisierten Studien war im Verlauf der letzten Jahre rückläufig und betrug etwa 3 % (▶ Tab. 1), was neben der zunehmenden Erfahrung der Internationalisten auch der Weiterentwicklung der Klappen und einer Abnahme der Größe der zur Implantation notwendigen Kathetersysteme geschuldet ist [4,20]. Für die TAVI-assoziierte Schlaganfallrate ist kein relevanter Unterschied aufgrund eines transfemoralen oder transapikalen Zugangswegs nachweisbar, wobei letzterer mit einem erhöhten Risiko für ein periprozedurales Vorhofflimmern assoziiert zu sein scheint [18].…”
Section: Transkatheter-aortenklappenimplantationunclassified
“…1) [5,43]. So finden sich (in Abhängigkeit von der Feldstärke und der DWI-Schichtdicke) beispielsweise bei 8-41 % aller Patienten nach linksatrialer Katheterablation und bei 40-93 % aller Patienten nach TAVI akute zerebrale Läsionen [5,20,21,29,43,44], deren mögliche Assoziation mit kognitiven Defiziten (trotz der Heterogenität der zumeist (weit) unter 100 Patienten umfassenden Kohorten) wiederholt postuliert wurde [3,5,43]. Auch wenn die diesbezügliche Relevanz noch nicht abschließend beurteilt werden kann, hat die Verwendung des zerebralen MRTs aus Sicht des Autors in einem relevanten Maße dazu beigetragen, das Embolierisiko kardialer Prozeduren zu visualisieren und Maßnahmen zur periprozeduralen Schlaganfallprävention zu erproben.…”
Section: Nachweis Zerebraler Ischämien Mittels Mrtunclassified